Health Education About the Importance of Antenatal Care During the COVID-19 Pandemic - Susanti, Susanti; Sari, Ika Novita (Indonesian Community Empowerment Journal, 2022)
Antenatal care is very important for pregnant women; mothers who do not do prenatal care have a higher risk of pregnancy complications and maternal death. The benefits of pregnancy tests are to detect complications such as preeclampsia, diabetes mellitus, gestational age, fetal growth, and maternal and fetal health. The purpose of this health education is to make participants aware of the importance of Antenatal care visits during pregnancy during the COVID-19 pandemic. This community service was carried out in October 2021 at BPM Suratmi, Batam City. Participants who were included in this activity were pregnant women who were willing to attend when the activity took place, as many as 14 participants. This form of community service activity is in the form of providing health education to pregnant women, with material on understanding Antenatal care, Antenatal care goals benefits of Antenatal care, Antenatal care examination standards, and the impact of not having Antenatal care visits. Counseling is presented with media in the form of laptops, infocus, power points, and brochures given to mothers. After completing the counseling activities, a pregnancy examination was carried out in accordance with the standard of examination, it was found that the results of the examination were good for the mother and fetus of all respondents. From the evaluation results, it was found that the respondents understood and understood the importance of antenatal care visits during the COVID-19 pandemic and the respondents were enthusiastic about the material presented, as seen from the questions given by the participants. It is hoped that mothers can carry out pregnancy checks according to the schedule of examinations to midwives or other health facilities regarding the state of physical and psychological health during pregnancy so that they can detect the development and health of the mother and fetus while still implementing strict health protocols during the COVID-19 pandemic.